A bio-inspired, ultra-tough, high-sensitivity, and anti-swelling conductive hydrogel strain sensor for motion detection and information transmission. Issue 12 (14th October 2022) - Di, Xiang; Hou, Jiawen; Yang, Mingming; Wu, Guolin; Sun, Pingchuan
Abstract : A bio-inspired, ultra-tough, high-sensitivity, and anti-swelling conductive hydrogel strain sensor for motion detection and information transmission. Abstract : Conductive hydrogels are excellent candidates for the next-generation wearable materials and are being extensively investigated for their potential use in health monitoring devices, human–machine interfaces, and other fields. However, their relatively low mechanical strength and performance degradation due to swelling have presented challenges in their practical application. Inspired by the multiscale heterogeneous architecture of biological tissue, a dynamic cross-linked, ultra-tough, and high-sensitivity hydrogel with a swelling resistance characteristic was fabricated by the principle of multiple non-covalent interaction matching and a step-by-step construction strategy. A heterogeneous structure was constructed by the combination of a 'soft' hydrophobic-conjugated micro-region structural domain with inter/intra-molecular hydrogen bonding and π–π stacking along with 'rigid' cross-linking via strong ionic coordination interactions. Reversible cross-linking synergies and variations in the content of rigid and flexible components guaranteed the hydrogel to undergo flexible and efficient modulation of the structures and gain excellent mechanics, including elongation at break (>2000%), toughness (∼60 MJ m −3 ), and recovery (>88%). Notably, hydrogels displayed good anti-swelling properties even in solutions with different pH (pH 2–11) and solvents. Moreover, the hydrogel further exhibited fast response (47.4 ms) and high sensitivity due to the presence of dynamic ions (Fe 3+, Na +, and Cl − ); therefore, it was assembled into a sensor to detect various human motions and used as a signal transmitter for the encryption and decryption of information according to Morse code. This study provides basis for the development of a variety of robust and flexible conductive hydrogels with multifunctional sensing applications in next-generation wearable devices.